The role of Forensic accounting in combating money laundering - a field study on the Kingdom of Saudi Arabia - in light of its accession to Financial Action Task Force (FATF) - Ismail, Salwa Hussein Roshdy; Mostafa, Fatimah Shoaib (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aimed to clarify the role of Forensic accounting in the development of accounting work mechanisms to combat money laundering operations, and how to benefit from the Kingdom of Saudi Arabia joining Financial Action Task Force (FATF) in that, the researchers relied on carrying out this research on the descriptive analytical approach and relied on the statistical packages for science program Statistical Package For Social Science (SPSS / Pc +) in hypothesis testing, sample analysis, data compilation, tabulation and analysis. The research found that there is a direct relationship between Forensic accounting services and its components and the accession of Saudi Arabia to Financial Action Task Force (FATF) and combating money laundering operations The research recommended to increase the activation of Forensic accounting programs in the Saudi Organization for Certified Public Accountants as well as business colleges of King Khalid University to contribute to the elimination of money laundering operations in line with the Kingdom’s current status as a permanent member of Financial Action Task Force (FATF).